2021
DOI: 10.1016/j.jhepr.2021.100282
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide population-based prospective study of cirrhosis in Iceland

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Neben der HBV-Infektion werden dort auch Ziele zur Bekämpfung der HCV-Infektion, wie etwa eine bessere Aufklärung oder der breitere Zugang zu Gesundheitsressourcen inklusive einer Therapie, beschrieben [ 18 ]. Eine Gruppe isländischer Autoren zeigte kürzlich, wie eine Steigerung des Alkoholkonsums sowie ein vermehrtes Auftreten von Adipositas und HCV-Infektionen in Island die früher sehr niedrige Leberzirrhoserate des Landes hat ansteigen lassen [ 17 ]. Im Umkehrschluss legen die Beobachtungen nahe, dass eine niedrige Prävalenz der genannten Faktoren zur Vermeidung von Leberzirrhosen beiträgt.…”
Section: Sonstige Präventionsprogrammeunclassified
“…Neben der HBV-Infektion werden dort auch Ziele zur Bekämpfung der HCV-Infektion, wie etwa eine bessere Aufklärung oder der breitere Zugang zu Gesundheitsressourcen inklusive einer Therapie, beschrieben [ 18 ]. Eine Gruppe isländischer Autoren zeigte kürzlich, wie eine Steigerung des Alkoholkonsums sowie ein vermehrtes Auftreten von Adipositas und HCV-Infektionen in Island die früher sehr niedrige Leberzirrhoserate des Landes hat ansteigen lassen [ 17 ]. Im Umkehrschluss legen die Beobachtungen nahe, dass eine niedrige Prävalenz der genannten Faktoren zur Vermeidung von Leberzirrhosen beiträgt.…”
Section: Sonstige Präventionsprogrammeunclassified
“…However, in these studies the age of the different etiologies was not particularly investigated. However, in recent prospective studies from Iceland, it was demonstrated that patients who were diagnosed with cirrhosis due to NAFLD were significantly older than patients with other etiologies ( 12 , 13 ). Interestingly, the mean age at diagnosis of alcoholic liver disease (ALD)- vs. NAFLD-cases was 58 vs. 64 years in 2010–2015 ( 12 ), and during the last 7 years [2016–2022], the mean age was 59 years in patients with ALD and 68 years in NAFLD patients ( 13 ).…”
mentioning
confidence: 99%
“…However, in recent prospective studies from Iceland, it was demonstrated that patients who were diagnosed with cirrhosis due to NAFLD were significantly older than patients with other etiologies ( 12 , 13 ). Interestingly, the mean age at diagnosis of alcoholic liver disease (ALD)- vs. NAFLD-cases was 58 vs. 64 years in 2010–2015 ( 12 ), and during the last 7 years [2016–2022], the mean age was 59 years in patients with ALD and 68 years in NAFLD patients ( 13 ). Thus, it seems obvious that many of these patients will have liver-related outcomes in their 70s or 80s and the results of the current study are therefore extremely relevant.…”
mentioning
confidence: 99%
“…1 Nýlega var birt rannsókn á nýgengi og orsökum skorpulifrar á Íslandi fyrir tímabilið 20102015. 2 Nýgengi skorpulifrar á þessu tímabili var 9,7 tilfelli fyrir hverja 100.000 íbúa. Það er þreföld aukning á nýgengi miðað fyrri rannsókn en var ennþá nokkru laegra en þekktist meðal annarra Norðurlandaþjóða.…”
unclassified